Exploring the Influence of Expatriation on Individual Identities and Shopping Behaviours in the UAE - Serap, Emik (2020)
With the arrival of globalization, the amount of expatriation is constantly increasing. While adjustment of expatriates to a new environment has gained great attention in literature, few studies are available on expatriate shopping behaviour. Particularly in the United Arab Emirates (UAE), where the expatriate population is much higher than the local population, studies on expatriation remain limited and tend to be descriptive in nature. Furthermore, a basic tenet of existing literature state that expatriates go through certain changes in identity when moving to a new social environment. Identity is recognized as a highly important factor in an expatriate’s psychosocial adjustment and health. The thesis’s questions include how expatriation influences individual identities and shopping behaviours to change, and why individuals go through changes in their identities and shopping behaviours when moving abroad and living an expatriate life? To answer these questions, this research explores the shopping behaviour of expatriate consumers, influenced by various factors in association with their shift in identity towards a new shopping behaviour. Hence, the output of this research developed a conceptual framework which identifies the factors that cause expatriate identity and shopping behaviour changes. This research explored the aims and questions through semi-structured interviews, gathering stories and experiences of 40 expatriate workers from various nationalities, between 21 to 65 years of age, that have been residing in the UAE up to five years. While the present research was conducted in the UAE, its applications may extend to all expatriates around the world. Findings of this research aim to help businesses further understand possible changes in expatriate shopping behaviour. Based on the type of products, findings of this research can be linked to marketing communications, advertising communications, product development, and relationship management. The main form of data collection was through interviewing participants. Overall, ten themes emerged from the gathered data describing expatriates’ general shopping habits, specifically from the aspect of their identities after moving abroad. The findings of this research shed light upon the fact that expatriation has a multi-dimensional impact on individuals’ shopping behaviour and identity. These impacts include, Social Environment and Peer Pressure, Social Media Usage, Changing Identity, Hedonic Shopping Factors, The Retail Therapy- Feelings of Loneliness, Stress and Boredom, Variety Festivals and Sales, First Impressions, Use of Luxury Products, Brands and Brand Engagement, Shopping as a Means of Socialization. Thus, this research explores and conceptualizes the influences of expatriation in change of individual identity and purchasing behaviour.